2014
DOI: 10.5811/westjem.2013.7.14945
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Guidelines and Best Practices: Recommendations from the Council of Residency Directors Social Media Task Force

Abstract: Social media has become a staple of everyday life among over one billion people worldwide. A social networking presence has become a hallmark of vibrant and transparent communications. It has quickly become the preferred method of communication and information sharing. It offers the ability for various entities, especially residency programs, to create an attractive internet presence and “brand” the program. Social media, while having significant potential for communication and knowledge transfer, carries with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 26 publications
0
41
0
2
Order By: Relevance
“…7 In 2012, the Council of Residency Directors in Emergency Medicine (CORD) strongly recommended that each residency program develop a social media policy, and that the content manager of a residency program's social media site should be a staff member, not a resident. 9 The Council's rationale was that content managers may not only be held personally liable for information posted to programs' social media sites, but also are responsible for ensuring compliance with the Health Insurance Portability and Accountability Act of 1996 (HIPAA), having postings use an appropriate professional tone, and portraying an accurate representation of the brand and public image of the programs and institutions they represent. 10,11 However, a recent survey of 14 EM residency programs showed that a number of them did not adhere to these guidelines, by either not having a social media policy in place or having residents serve as content managers for social media accounts.…”
Section: Introductionmentioning
confidence: 99%
“…7 In 2012, the Council of Residency Directors in Emergency Medicine (CORD) strongly recommended that each residency program develop a social media policy, and that the content manager of a residency program's social media site should be a staff member, not a resident. 9 The Council's rationale was that content managers may not only be held personally liable for information posted to programs' social media sites, but also are responsible for ensuring compliance with the Health Insurance Portability and Accountability Act of 1996 (HIPAA), having postings use an appropriate professional tone, and portraying an accurate representation of the brand and public image of the programs and institutions they represent. 10,11 However, a recent survey of 14 EM residency programs showed that a number of them did not adhere to these guidelines, by either not having a social media policy in place or having residents serve as content managers for social media accounts.…”
Section: Introductionmentioning
confidence: 99%
“…All communication between the patient and physician, whether in person or online should follow the standards for professional interactions which involves rights and obligations for both parties 15 . Publishing photos and videos of patients on social media without their consent are the breach of confidentiality and privacy of the patient 14 . A survey reported lack of knowledge regarding the ethical issues of using social media by medical students and residents whereat least 12 instances of potential patient violations occurs by posting photographs of care they provided to individuals during a medical mission.…”
Section: Breaches Of Confidentialitymentioning
confidence: 99%
“…Challenges in social media usage While social media serves a great advantage to the medical professions, at the same time carries a greater risk in terms of legal, ethical, personal, and professional aspects 14 . Therefore, physicians and medical students using social media should pay attention to the ethical sensitivity in their relationships with patients 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Published guidelines on using social media provide a useful platform for the safe exchange of medical knowledge. (Pillow et al, 2014) Residency programs should revise their curriculum to incorporate such guidelines and capitalize on the power of social media into a stronger and modern system.…”
Section: Resultsmentioning
confidence: 99%